The Effectiveness of an Interactive Biology E-Module in Enhancing Eleventh-Grade Senior High School Students’ Scientific Literacy - Nia Afrilia; Christina Ismaniati (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
Scientific literacy is an essential competency in biology learning, particularly in understanding abstract physiological concepts such as the human excretory system. This study aimed to examine the effectiveness of an interactive biology e-module in improving eleventh-grade students’ scientific literacy on the topic of the human excretory system. Scientific literacy was measured through students’ ability to explain scientific phenomena, interpret scientific data and evidence, apply scientific concepts in daily life, and construct scientific arguments. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The participants consisted of two eleventh-grade classes at SMA Negeri 2 Yogyakarta, each involving 36 students as the control and experimental groups. The research instrument was a 15-item scientific literacy test that had been validated and demonstrated a Cronbach’s Alpha reliability coefficient of 0.859. Data were analyzed using descriptive statistics, normality tests, homogeneity tests, independent samples t-tests, and N-Gain analysis. The findings revealed that the experimental group achieved higher learning improvement than the control group, with an N-Gain score of 0.78 categorized as high, while the control group obtained 0.69 categorized as moderate. The posttest results showed a significant difference between the two groups with a p-value of 0.006. These findings indicate that the interactive biology e-module is effective in improving students’ scientific literacy on the human excretory system topic.